2015
DOI: 10.1093/bjsw/bcv115
|View full text |Cite
|
Sign up to set email alerts
|

‘It's All a Bit Pantomime’: An Exploratory Study of Gay and Lesbian Adopters and Foster-Carers in England and Wales

Abstract: This paper reports the findings of a study identifying the experiences of gay and lesbian adopters and foster carers in England and Wales. Qualitative interviews were conducted with twenty-four lesbians and gay men who had undertaken any part of the adoption or fostering application process since the implementation of the Adoption and Children Act of 2002. The study suggests that whilst increasing numbers of lesbians and gay men are accessing fostering and adoption services, gender and sexuality are still prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…Participants observed that professional discourses around family, kinship, or parenting were sometimes implicitly heteronuclear in their construction. As illustrated within previous findings (Wood, 2016), this meant that gay and lesbian applicants often disrupted the heterogendered underpinnings of adoption or fostering processes.…”
Section: Making the Decision To Fostermentioning
confidence: 72%
See 3 more Smart Citations
“…Participants observed that professional discourses around family, kinship, or parenting were sometimes implicitly heteronuclear in their construction. As illustrated within previous findings (Wood, 2016), this meant that gay and lesbian applicants often disrupted the heterogendered underpinnings of adoption or fostering processes.…”
Section: Making the Decision To Fostermentioning
confidence: 72%
“…Similarly, participants' kinship networks were often viewed through a biogenetic lens, sometimes at the expense of families of choice. Narratives demonstrate that the recognition of “family” remains highly dependent upon wider dominant cultural meanings and that those experiences situated beyond heteronormative models of parenthood may be rendered invisible within such processes (Hicks, ; Finch, ; Wood, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing numbers of lesbian women and gay men are accessing fostering and adoption services. Kate Wood13 points out that gender and sexuality are still problematic areas of contestation within this context. LGBTQ foster parents and foster-to-adopt families have also received relatively little attention in the published literature.…”
Section: Introductionmentioning
confidence: 99%